Fingolimod and macular edema: Pathophysiology, diagnosis, and management - Cugati, Sudha (Neurol Clin Pract, 2014)
Fingolimod causes macular edema (ME) by acting via the S1P3 receptor agonism, thereby reducing the tight junction between the endothelial cells of the retinal capillaries. This results in the breakdown of the inner blood retinal barrier, causing ME. Ophthalmologic evaluation including optical coherence tomography is recommended at baseline and then at 3 months, 6 months, and annually thereafter in all patients on fingolimod. The risk of ME increases in patients who are diabetic, have had uveitis, or who undergo intraocular procedures such as cataract surgery, and hence these patients need close monitoring. Cessation of the drug results in resolution of the ME. However, ME can also be treated using anti-inflammatory medication (steroids) in patients who opt to remain on fingolimod.